THE EFFECTIVENESS OF CEMCEM (Spondiaspinnata (L.f) Kurz) LEAF EXTRACT IN INHIBITING THE GROWTH OF Streptococcus mutans - Putu Sulistiawati Dewi; I Made Merta Suparka (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2023)
Introduction: Dry socket is post-tooth extraction pain characterized by partial or complete loss of blood clots in the alveolar socket. One of the management of dry socket is by using antibiotic therapy. Inappropriate use of antibiotics in addition to being economically wasteful can also cause bacterial resistance to antibiotics. The use of herbal ingredients such as Cemcem (Spondiaspinnata (L.f) Kurz) is one solution. Cemcem leaves are thought to have antibacterial effects because they contain flavonoids, tannins and saponins. This study aims to determine the inhibition of cemcem leaf extract (Spondias pinnata (L.f) Kurz) against the growth of Streptococcus mutans. Materials and methods: The research method used is the Kirby Bauer method which is a sensitivity test with the agar diffusion method using the disc diffusion technique. In the Kirby Bauer sensitivity test using selective media, namely Muller Hinton Blood Agar media, the inhibition zone created is characterized by a clear zone around the disc. The data obtained were analyzed using the Kruskall Wallis test to determine whether or not there was a significant difference then continued with the Mann Whitney U - Test. Results: Cemcem leaf extract (Spondias pinnata (L.f) Kurz) with a concentration of 60% and 70% can inhibit the growth of Streptococcus mutans better than positive control and 80% concentration. Conclusion: 60% concentration of cemcem leaf extract is more effective in inhibiting the growth of Streptococcus mutans than 70% and 80% concentrations.